Production process of spherical alumina powder with high purity and low uranium content

By employing a multi-step process involving tiered pickling, hydrothermal intensification, and particle size distribution, the problem of reducing uranium content in spherical alumina powder has been solved, enabling the production of high-purity, low-uranium-content spherical alumina powder. This powder is suitable for packaging materials of highly integrated integrated circuits, improving the reliability and lifespan of electronic devices.

CN121044609APending Publication Date: 2025-12-02ZHEJIANG HUAFEI ELECTRONICS BASE MATERIAL
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202511159072.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-19
Publication Date
2025-12-02

AI Technical Summary

Technical Problem

In existing technologies, it is difficult to stably reduce the uranium content of spherical alumina powder to an ultra-low level. Traditional acid washing is inefficient, uranium encapsulation is severe during spheroidization, and the spheroidization and uranium removal processes are disconnected, which affects the reliability and lifespan of semiconductor devices.

Method used

A three-stage uranium removal system, consisting of cascade acid washing, hydrothermal enhancement, and particle size optimization, is employed. Through multi-step collaborative innovation, including flame melting and spheroidization, cascade chemical acid washing, hydrothermal enhancement, and particle size distribution, the uranium content is ensured to remain consistently below 30 ppb.

Benefits of technology

It achieved a stable uranium content below 10 ppb, significantly reducing alpha ray contamination, improving the reliability and lifespan of semiconductor packaging materials, and meeting the high purity requirements of highly integrated integrated circuits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a production process of spherical alumina powder with high purity and low uranium content, which comprises the following steps: by taking angular alumina with the uranium content of 50-100ppb as a raw material, sequentially carrying out flame melting spheroidization, gradient pickling, hydrothermal strengthening uranium removal, wet grading coarse grain removal, low-temperature drying and airflow depolymerization to finally obtain the finished product spherical alumina powder with the uranium content of less than 30ppb. Through a multi-stage uranium removal system including incoming material management and control, gradient pickling, hydrothermal coupling and particle size optimization, the traditional single pickling efficiency bottleneck is broken through, and deep dissolution of lattice uranium and effective removal of coarse-grain uranium enrichment nuclei are achieved; the morphology and the specific surface are locked through whole-process low-temperature hydrothermal and low-shear drying, so that the powder is ensured to be used as a filler in resin sealing materials of high-integration integrated circuits, large-scale integrated circuits and super-large-scale integrated circuits, and the powder has the comprehensive performance of high filling, low thermal resistance and zero alpha-ray soft errors; and the limit requirements of node packaging materials of 3nm and below are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of inorganic non-metallic material preparation technology, specifically to a production process for high-purity, low-uranium-content spherical alumina powder. Background Technology

[0002] Spherical alumina powder is widely used as a key thermally conductive filler in epoxy resin encapsulation materials for highly integrated circuits (ICs), large-scale integrated circuits (LSIs), and very large-scale integrated circuits (VLSIs) due to its excellent flowability, high filling rate, low wear, and good thermal conductivity. However, trace amounts of radioactive elements (such as uranium U) in the encapsulation material can release alpha rays, causing soft errors in semiconductor memories, which seriously affect the reliability and lifespan of electronic devices.

[0003] In existing technologies, the production of spherical alumina mainly employs flame melting. Acid leaching is commonly used to reduce uranium content. However, traditional methods, relying solely on a single acid leaching process, are inefficient. This limited effectiveness in removing uranium deeply embedded within the powder or in specific deposition states makes it difficult to consistently achieve ultra-low uranium levels. Furthermore, the spheroidization process is disconnected from uranium removal; the surface of the spheroidized powder undergoes melting and recrystallization, forming a dense layer that hinders the effective erosion of internal impurities by subsequent acid solutions. Hydrothermal treatment is underutilized. While it has applications in impurity removal, there is a lack of systematic process design and parameter optimization to integrate it with the characteristics of flame-melted spheroidized powder, particularly for deep dissolution and extraction of uranium. Additionally, large particle removal and particle size distribution typically focus only on physical properties, neglecting the potential differences in uranium removal efficiency between powders of different particle sizes.

[0004] Therefore, there is an urgent need and significant value in developing an innovative process that can effectively overcome the above-mentioned defects and achieve stable and efficient production of high-purity (especially ultra-low uranium content) spherical alumina powder. Summary of the Invention

[0005] The purpose of this invention is to provide a production process for high-purity, low-radioactivity spherical alumina powder for semiconductor packaging, solving the core problems in the prior art such as incomplete uranium removal, uranium encapsulation during the spheroidization process, and low acid washing efficiency.

[0006] This invention's production process, through multi-step collaborative innovation, systematically solves the industry challenge of alpha-ray contamination in high-end electronic packaging materials. While ensuring high purity, high sphericity, and controllable particle size in spherical alumina, it achieves an ultra-low radioactivity level with uranium content consistently below 30 ppb. Traditional acid leaching methods have low efficiency in removing uranium from the crystal lattice (typically >50 ppb). This process, through a three-stage uranium removal system of gradient acid leaching, hydrothermal enhancement, and particle size optimization, overcomes the challenge of deep uranium removal, stabilizing the uranium content at 1-30 ppb, filling the industry gap in ultra-low alpha-ray spherical alumina.

[0007] This invention provides a process for producing high-purity, low-uranium-content spherical alumina powder, comprising the following steps: Step 1. Provide alumina and aluminum hydroxide micronized raw materials with a uranium content of 50-100 ppb and a D50 of 1-100 μm; control the risk of uranium contamination from the source and avoid excessive burden on subsequent processes. Using aluminum hydroxide micronized powder as an optional raw material balances cost and reactivity, making the process compatible with fluctuations in the upstream supply chain; the particle size range ensures uniform melting during flame melting, as excessively fine powder is prone to volatility, while excessively coarse powder results in incomplete spheroidization.

[0008] Step 2. The alumina micro powder and aluminum hydroxide micro powder are subjected to flame melting and spheroidization treatment to obtain primary spherical alumina powder. The powder is then melted at a high temperature above 2000℃, causing angular or irregular particles to shrink into perfect spheres under the action of surface tension. The melt-quench process eliminates internal pores and cracks, forming a dense and smooth surface and reducing the specific surface area. The extremely rapid cooling inhibits the excessive growth of the γ→α phase transformation, maintaining fine and high-purity α-Al2O3 grains and ensuring a high thermal conductivity framework. The high-temperature zone causes low-melting-point uranium-containing and alkali metal impurities to volatilize or migrate to the surface, providing an "accessible" impurity layer for subsequent step-by-step acid / alkali washing. Flame melting and spheroidizing transforms micro-powder into powder with high sphericity (>95%), improving subsequent encapsulation filling rate and thermal conductivity. Spheroidization is the foundation of functionality; spherical particles have good flowability, which can increase the resin filler rate. The melting process causes some surface uranium to volatilize, and the increased surface microcracks after spheroidization facilitate the penetration of acid or alkali solutions. The dense but non-vitrified surface prevents uranium from being completely encapsulated and avoids excessive corrosion by acid / alkali solutions, ensuring maximum efficiency of the cascade purification process.

[0009] Step 3. The primary spherical alumina powder obtained in Step 2 is purified by step-by-step chemical acid washing or alkaline washing. Step-by-step chemical acid washing involves two stages of directional uranium removal: the first stage is strong acid washing (pH ≤ 2.0) to strip surface uranium and impurities (removing 60-70% of uranium); the second stage is medium acid washing (pH = 2.0-4.0) to dissolve uranium at the lattice edges using the oxidizing properties of nitric acid (further removing 20-25% of uranium). This addresses the shortcomings of single acid washing: strong acids can only treat the surface, while weak acids cannot open channels; the gradient pH design avoids excessive corrosion of the powder. When upstream raw materials have few acid-soluble impurities and many alkali-soluble impurities, alkaline washing can replace or partially replace acid washing, avoiding excessive acid consumption and equipment corrosion; strong alkalis such as NaOH and KOH have a much lower corrosion rate on the Al2O3 matrix than on common associated impurities such as SiO2 and Fe2O3, allowing preferential dissolution of these uranium-containing support phases (such as silicate inclusions) without damaging the spherical framework; high concentrations of OH in the alkaline solution... - Can react with uranyl ions UO2 2+ Forms soluble [UO2(OH)4] 2- Complexes promote deep desorption of uranium from grain boundaries or microcracks; after alkaline washing, abundant Al-OH groups are formed on the particle surface, providing active sites for subsequent hydrothermal uranium removal steps and improving the uranium migration efficiency in the hydrothermal stage; alkaline washing purification can also achieve targeted removal of impurities that are insoluble in acid but soluble in alkali (such as some aluminosilicates), reducing the overall impurity load.

[0010] Step 4. Hydrothermal enhanced uranium removal from the powder obtained in Step 3: The hydrothermal reaction is carried out at 150-180℃ for 3-12 hours, followed by thorough washing. Under the hydrothermal environment of 150-180℃, the permeability of water molecules is increased by more than 10 times, deeply dissolving uranium within the crystal lattice. The high temperature promotes the desorption of uranium from the Al2O3 crystal lattice, removing "stubborn uranium" that acid washing cannot resolve. The uranium content is further reduced by 50-70% after hydrothermal treatment, a key step in achieving <10 ppb. Hot water at 150-180℃ promotes local hydrolysis and breakage of Al-O-Al bonds, causing micro-expansion of the crystal lattice and opening channels for uranium ion diffusion. This exposes and dissolves "lattice uranium" that cannot be reached by acids / alkalis, further improving the uranium removal rate. The hydrothermal environment promotes slight recrystallization on the surface and near-surface areas. Uranium impurities are expelled into the solution during the dissolution-rearrangement process, achieving deep purification with almost no loss of sphericity and particle size, maintaining subsequent high filling capacity and low thermal resistance performance. High-temperature, high-pressure water and residual OH... - / Acid radical synergy forms soluble uranyl complex ions, further reducing the activity of solid-phase uranium, avoiding the introduction of additional complexing agents, reducing chemical residues, and reducing the difficulty of wastewater treatment; inhibiting secondary sintering or excessive hydroxylation of particles, maintaining sphericity and specific surface area, ensuring that the powder still has excellent flowability and resin compatibility after drying and depolymerization, meeting the high-integration packaging process window.

[0011] Step 5. Perform particle size sorting and gradation on the powder obtained in Step 4: remove large particles and grade them according to the target particle size distribution; remove large particles, the uranium residue inside these particles is 3 to 5 times the average value; optimize the mixing ratio of particle size gradation according to specific surface area to balance the uranium removal effect and filling rate; removal of large particles can reduce the overall uranium content by 15 to 20%; gradation optimization avoids too much fine powder, as a large specific surface area will lead to a high risk of residue, balancing performance and purity.

[0012] Step 6. The graded powder is dehydrated, dried, and post-treated to obtain finished spherical alumina powder with a uranium content of less than 30 ppb. Dehydration and drying avoid high-temperature sintering (<100℃) and prevent uranium re-adsorption. Airflow pulverization removes soft agglomerates and ensures powder dispersibility. Low-temperature drying retains the clean surface after hydrothermal treatment. The final product has improved flowability, reaching the top level in the industry.

[0013] This process, through multi-step innovative design, deeply integrates materials science (lattice uranium removal), chemical engineering (gradient acid / alkali washing), and particle technology (particle size optimization), achieving not only technological breakthroughs but also significant economic and strategic value. Specifically, the graded acid / alkali washing opens powder penetration channels for hydrothermal treatment, hydrothermal enhancement relies on acid pre-cleaning, and particle size control removes large residual uranium particles that are difficult to treat with acid / hydrothermal methods.

[0014] Step 3 of this invention, a tiered chemical acid leaching purification process, achieves highly efficient and deep removal of uranium impurities through the synergistic effect of two-stage acid leaching and precise parameter control. Traditional single-stage acid leaching processes have fundamental flaws: while strong acid (pH ≤ 2.0) removes uranium quickly from the surface, it also causes severe powder dissolution and fails to address uranium within the crystal lattice; conversely, weak acid (pH > 4.0) fails to open surface channels, resulting in insufficient uranium removal. This invention's tiered design integrates "strong acid surface stripping" and "weak acid deep treatment," overcoming both rapid surface uranium removal and efficient dissolution of lattice-bound uranium, while controlling powder loss to <2%. The first-stage strong acid achieves "physical cell wall disruption + surface uranium removal"; the second-stage weak acid completes "chemical swelling + lattice uranium dissolution"; the two stages synergistically cover all uranium occurrence states (free state, adsorbed state, and lattice-bound state). This progressive purification strategy not only enabled the uranium removal rate to exceed 85%, but also became the core technological support for achieving the ultra-low radioactivity target of U≤10ppb, filling the key technological gap in the localization of high-end semiconductor packaging materials.

[0015] In the production process of this invention, step 3, acid washing and purification, includes the following specific steps: Step 3.1 First-stage acid washing: Adjust the pH of the slurry to ≤2.0 using an acid solution with a concentration of 2~6 mol / L, and stir the reaction at 50~80℃ for 1~3 hours; the first-stage acid washing achieves surface stripping, using a high-concentration acid (2~6 mol / L) to rapidly dissolve the free uranium salts (such as UO2) on the powder surface. 2+ ), and high concentration of H + Attacking the hydroxyl groups on the alumina surface opens micron-sized pores, creating conditions for subsequent penetration; this stage can remove 60-70% of uranium impurities, preparing for subsequent deep processing. If this step is skipped and weak acid treatment is performed directly, the uranium removal rate drops sharply.

[0016] Step 3.2 Second-stage pickling: After washing, adjust the pH of the slurry to 2.0-4.0 using an acid solution with a concentration of 0.5-2 mol / L, and stir the reaction at 60-90℃ for 4-12 hours; the second-stage pickling achieves deep penetration. After the first-stage pickling and thorough washing, use a medium-concentration acid (0.5-2 mol / L) to adjust the pH to a weakly acidic range of 2.0-4.0, preferably nitric acid (HNO3) as the acid source, utilizing NO3. - The strong oxidizing properties of tetravalent uranium (U) 4+ (Insoluble in acid) is converted into hexavalent uranium (U 6+ (Easily soluble), significantly improving the dissolution efficiency of uranium bound to the lattice edge; raising the pH to 2.0~4.0 can avoid excessive corrosion of the powder by strong acid, and the powder dissolution loss is >5% when pH < 1.0, while the slight increase in temperature accelerates the oxidation reaction kinetics.

[0017] Step 3.3 After pickling, wash thoroughly to ensure impurity desorption. After each pickling stage, rinse repeatedly with deionized water until the conductivity is <5μS / cm to ensure the absence of acid radical ions (Cl). - NO3 - SO4 2- Residual ions may remain; if acid radicals remain, uranium ions will recombine during subsequent hydrothermal steps; residual chloride ions will corrode semiconductor packaged metal circuits and must be completely removed.

[0018] In the production process of this invention, the inorganic acid mentioned in step 3.1 is hydrochloric acid, nitric acid, or sulfuric acid, and the pH is adjusted to ≤1.5; the acid selection includes hydrochloric acid, nitric acid, sulfuric acid, or organic acids, with each strong acid having its own advantages: hydrochloric acid (HCl) has the lowest cost, Cl... - It has strong solubility for surface uranium salts (such as UCl4); nitric acid (HNO3) has both acidic and oxidizing properties, and can initially convert U. 4+ For U 6+ Sulfuric acid (H2SO4) has a high boiling point and is suitable for high-temperature pickling; SO4 2- Uranyl ion (UO2) 2+It has a coordination effect. The isoelectric point (IEP) of alumina is pH≈9.0. When pH≤1.5, the powder surface carries a strong positive charge (Zeta potential > +35mV), which repels uranyl cations (UO2) through electrostatic repulsion. 2+ This promotes uranium detachment from the surface; for every 0.5 unit decrease in pH, the uranium leaching rate increases twofold. The carboxyl group (-COOH) of organic acids (such as oxalic acid, citric acid, and tartaric acid) reacts with uranyl ions (UO2). 2+ It forms stable water-soluble complexes (such as uranyl oxalate) with binding constants as high as 10. 8 Significantly improves uranium dissolution efficiency; avoids residual Cl in inorganic acids (HCl / HNO3). - / NO3 - The resulting corrosion of semiconductor metal wiring meets the extreme requirements of 3nm chips for ion residue; the organic acid dissociation constant can achieve a strongly acidic environment with pH≤2.0, while the corrosion inhibition effect reduces powder dissolution loss and ensures the integrity of the spherical structure.

[0019] The inorganic acid mentioned in step 3.2 is nitric acid or a mixture of hydrochloric acid and nitric acid; nitric acid or a mixture of acids is used for uranium removal with oxidation depth. Nitric acid (HNO3) contains NO3. - It decomposes at 60-90℃ to produce atomic oxygen, oxidizing inert tetravalent uranium to soluble hexavalent uranium; a hydrochloric acid / nitric acid mixture (preferably 1:1), Cl - HNO3 enhances the complexation ability of uranyl ions, providing an oxidant and synergistically increasing uranium solubility by 3 times. The pH range of 2.0–4.0 is U 6+ The optimal solubility window for UO2 is when pH < 2.0. 2+ It is easily hydrolyzed and precipitated; its solubility decreases by 70% when pH > 4.0; mild acidity reduces powder dissolution loss to < 1%. In the second-stage pickling in step 3.2, oxalic acid (H2C2O4) in the organic acid (specifically oxalic acid and citric acid) decomposes at 60~90℃ to generate oxidizing free radicals (·COO). - ), will inert tetravalent uranium (U 4+ ) is oxidized to soluble hexavalent uranyl (UO2) 2+ The oxidation efficiency is higher than that of nitric acid (because there is no NO3). - Byproduct competition); organic acid carboxyl groups and UO2 2+ Formation of five-membered ring chelates (such as uranyl oxalate [UO2(C2O4)2]) 2- The stability constant is much higher than that of chlorine complex, which completely blocks the redeposition of uranium on the powder surface; citric acid forms a buffer system in the pH range of 2.0 to 4.0 to maintain the optimal uranium dissolution environment and avoid local over-acid damage to the powder.

[0020] The thorough washing described in step 3.3 specifically includes: after each acid wash, washing with a large amount of deionized water 3-8 times until the washing solution is nearly neutral and the conductivity meets the standard, thoroughly removing residual acid radicals and dissolved impurity ions. The first wash removes 90% of the free acid / alkali solution, and subsequent washes remove adsorbed ions. Experiments show that the uranium ion desorption rate is >99% after the 4th wash; if the washing is less than 3 times, residual NO3 remains. - Uranyl nitrate precipitate will form during the hydrothermal step, which will increase the uranium content. Setting the endpoint conductivity to ≤5μS / cm (equivalent to ion residue <1ppm) can avoid Cl - Corrosion of semiconductor copper wiring prevents residual acid radicals from recombining with uranium (such as forming (UO2)2SO4 precipitate).

[0021] After staged acid leaching, the residual uranium content is precisely controlled within the range of 15-30 ppb. If it exceeds this range (>50 ppb), subsequent hydrothermal treatment will struggle to reduce the uranium content below 10 ppb (due to the limited internal uranium diffusion rate). The nitric acid waste liquid from the second-stage acid leaching can be concentrated and recycled for the first-stage acid leaching, reducing waste acid treatment costs. The gradient pH design narrows the final uranium content fluctuation range to ±3 ppb (compared to ±15 ppb in traditional processes), meeting the stringent requirements for material uniformity in 3nm chips.

[0022] The combination of temperature (165~175℃) and time (4~12 hours) parameters for hydrothermal enhanced uranium removal in step 4 of this invention is essentially about finding the optimal solution between "powder structure stability" and "uranium deep removal efficiency" by precisely controlling the ionic activity of water and uranium diffusion kinetics.

[0023] In the production process of this invention, the hydrothermal reaction temperature in step 4 is 165~175℃, and the reaction time is 4~12 hours. The desorption activation energy of uranium (U) in the Al2O3 lattice is 120kJ / mol, and 165℃ is the critical point for triggering deep desorption; below this temperature, the desorption rate decreases exponentially; above 165℃, the ion product (Kw) of liquid water increases to 10. -11 (10 at 25℃) -14 ), H + A tenfold increase in concentration significantly enhances the solubility of uranium. Temperatures above 175℃ cause a phase transition in alumina, resulting in a sharp decrease in specific surface area, which conversely reduces uranium desorption efficiency. The uranium diffusion control mechanism indicates that the diffusion coefficient D for uranium migration from the interior of the Al₂O₃ lattice to the surface is 1.2 × 10⁻⁶. -16 m 2 / s (at 165℃), it is calculated that it takes ≥3.8 hours to complete deep migration (Fick's second law); after 4 hours, the uranium leaching rate approaches saturation (>95%). For raw materials with D100=100μm (uranium diffusion path up to 50μm), 12 hours are required to ensure the leaching of core uranium.

[0024] Step 3, the stepwise acid washing, provides an ideal precursor environment for the hydrothermal step. After acid washing, the uranium content is controlled at 15-30 ppb. The hydrothermal reaction in step 4 can reduce it to 5-8 ppb. At the same time, the acid radicals are thoroughly removed by washing, avoiding the formation of uranyl nitrate precipitate (UO2(NO3)2·6H2O) during hydrothermal treatment. The surface micropore channels are opened, and high-temperature water molecules can penetrate deep into the crystal lattice along the channels, enhancing the penetration depth.

[0025] The hydrothermal enhanced uranium removal process in step 4 of this invention maximizes the hydrothermal chemical effect under high temperature and high pressure through reactor engineering design and solid-liquid mass transfer optimization. Specifically, step 4 of the production process includes: transferring the powder slurry, purified by step-by-step acid washing and thoroughly washed, to a high-pressure reactor; adding an appropriate amount of deionized water; controlling the solid-liquid ratio at 1:2~1:15 w / w; conducting a hydrothermal reaction for 4~12 hours at a temperature of 165~175℃ and the corresponding saturated vapor pressure; after the hydrothermal reaction is completed, allowing it to cool naturally, removing the slurry, and washing it again thoroughly with deionized water until neutral.

[0026] The solid-liquid ratio is controlled at 1:2 to 1:15 w / w. The lower limit of 1:2 is suitable for nanoscale powders to ensure that the powder is fully dispersed and to avoid local overheating that could lead to phase transformation. The upper limit of 1:15 prevents excessive water dilution of uranium concentration, which could affect dissolution kinetics, while also taking into account thermal efficiency.

[0027] At 165-175℃ and corresponding saturated vapor pressure, the high-pressure environment produces a triple effect: the dielectric constant of water decreases, enhancing its solvation ability for uranium ions; high-pressure water permeates the interstitial spaces of the crystal lattice, causing the Al-O bond length to expand and releasing lattice uranium; and uranium hydrolysis precipitation is inhibited, resulting in UO2. 2+ The critical pH for hydrolysis is increased.

[0028] Rapid cooling causes an amorphous layer to form on the powder surface, encapsulating the uranium that has not diffused out; slow cooling at 0.5~1℃ / min allows uranium ions to continue migrating into the liquid phase, and the cooling process can remove residual uranium.

[0029] Step 4 utilizes precise control of the solid-liquid-thermal-pressure multiphase coupling within the reactor to optimize the solid-liquid ratio, resolving the contradiction between mass transfer and energy consumption. Saturated vapor pressure self-balancing activates the supersolventization capability of water, while natural cooling and slow release enable deep uranium migration. This process achieves the theoretical limit for hydrothermal uranium removal efficiency. Combined with the staged acid washing in Step 3, it constitutes an industrial-scale technology system capable of achieving uranium content down to 5 ppb.

[0030] This step forms an efficient cycle with the previous processes. The hydrothermal reaction in step 4 causes the lattice of small and medium-sized powders in the low α phase to expand, and uranium migrates to the surface. During gradation, the risk of uranium residue bound to the lattice of small and medium-sized powders is reduced. Particles with D50 > 45μm separated by hydrocyclone can be returned to the flame spheroidization step in step 2 for reprocessing, with a recovery rate > 95%, achieving zero waste of raw materials. The gradation data reversely controls the acid washing process. When the proportion of fine powder increases, the acid washing time is automatically shortened. Fine powder has a large specific surface area and a fast acid etching rate, reducing production costs.

[0031] In the production process of this invention, the removal of large particles in step 5 refers to the removal of particles with a diameter greater than the target D97~D100 value; the particle size distribution is optimized by considering the specific surface area of ​​powders of different particle sizes and the risk of impurity residue. During the hydrothermal reaction, high-temperature and high-pressure water molecules cannot penetrate into the interior of the crystal lattice at such a depth, resulting in the uranium residue concentration in the core region of these large particles being as high as 3 to 5 times the average value. Real-time removal of coarse particles exceeding the target D90 value ensures that when D90 ≤ 30 μm is required, all particles > 30 μm are separated, avoiding uranium content "hot spots" exceeding the standard caused by local coarse particle aggregation.

[0032] Particle size distribution is not a simple physical mixing process, but rather a precise calculation based on a specific surface area-uranium residue correlation model. The coarse powder (20~45μm) has a specific surface area of ​​only 0.1~0.2m². 2 / g, with the lowest risk of uranium residue, it fulfills the framework function, accounting for 60-70%, ensuring a high filling rate; the specific surface area of ​​medium powder (5-20μm) increases to 0.2-0.3m². 2 / g, its lattice defect regions are prone to uranium enrichment, with residual amounts eight times that of coarse powder. The proportion must be strictly controlled to <20%, exceeding this will result in a uranium content >10ppb in the product; fine powder (0.2~5μm) has a specific surface area as high as 0.3~15m². 2 Although surface uranium is easy to remove, excessive amounts can lead to the risk of uranium agglomeration and enrichment. The proportion is precisely locked at 10-20%.

[0033] In the production process of this invention, step 5, removing large particles, specifically includes: using wet classification technology to remove particles larger than the target value D97~D100 from the hydrothermal washed powder slurry; the wet classification technology includes hydrocyclones and centrifugal sedimentation classifiers. In the turbulent separation mechanism of the hydrocyclone, the centrifugal force field is enhanced, and the slurry enters the hydrocyclone at a tangential velocity of 15~20 m / s, forming a forced vortex flow field (centrifugal acceleration > 200g), causing particles >45μm to spiral down the wall to the underflow inlet; the particle size cutting accuracy is achieved by adjusting the feed pressure (0.2~0.5MPa) and the underflow inlet diameter (Φ5~10mm), achieving a precise separation of ±2μm (an improvement over dry sieving accuracy).

[0034] The laminar sedimentation control of the centrifugal sedimentation classifier applies Stokes' law. In a sedimentation tank with low-speed rotation (100~500rpm), by controlling the rotation speed and slurry viscosity, particles with a D90 value greater than the target value are preferentially sedimented. The ultrafine separation capability can separate particles with a D90=10μm into particles with a D90 value greater than 12μm (accuracy ±0.5μm).

[0035] The two devices are used in series: a hydrocyclone for coarse separation (removing particles >45μm) and centrifugal sedimentation for fine separation (removing particles >target D90 value), balancing efficiency and precision. The separated particles exceeding the standard are returned to step 2, the spheroidization step, achieving a utilization rate >95% and reducing raw material costs.

[0036] Solid content control: Before grading, the solid content of the slurry is adjusted to 15-25 wt% to ensure the optimal conveying condition with a viscosity of 30-50 cP; this avoids false large particle misjudgment caused by fine powder agglomeration. The dispersant added is 0.1% sodium polyacrylate (PAA) to keep the zeta potential < -40 mV, inhibiting particle flocculation.

[0037] This step utilizes a three-pronged design of physical separation, intelligent control, and resource recycling. At the physical level, it leverages the complementary effects of centrifugal force and laminar sedimentation to overcome the challenge of removing uranium-enriched nuclei larger than 45 μm. At the control level, dynamic regulation ensures particle size distribution accuracy meets atomic-level chip requirements. At the recycling level, excess particles are recycled in a closed loop, reshaping the paradigm of sustainable manufacturing of electronic materials.

[0038] In the production process of this invention, the dehydration operation in step 6 includes pressure filtration and centrifugal filtration; the drying is low-temperature drying, including spray drying and vacuum drying; the post-treatment is depolymerization treatment, including mechanical stirring and air jet milling. The dehydration process mainly terminates the reaction and optimizes energy consumption by rapidly separating the liquid and solid phases, cutting off the uranium re-adsorption channel, and providing a low-moisture filter cake for subsequent drying. The pressure filtration operation uses a diaphragm filter press with a filter cloth pore size ≤1μm, a filter cake solid content of 50~55%, a large throughput, and is suitable for continuous production. The centrifugal filtration uses a horizontal screw centrifuge with a centrifugal force ≥2000g and a residence time <5min, significantly reducing U. 2+ Backflow dynamics window.

[0039] Low-temperature drying is used for morphology locking and purification solidification. Residual free water is completely removed at temperatures below the α-Al₂O₃ phase transition temperature (<120℃), maintaining specific surface area and pore structure, and preventing uranium re-encapsulation caused by surface densification. Specifically, the spray drying inlet air temperature is 110~120℃, the outlet temperature is <80℃, the sphericity retention rate is >95%, and there is no hard agglomeration of particles. Vacuum drying has a vacuum degree ≤-0.09MPa, a drying temperature of 80~100℃, and low oxygen partial pressure, inhibiting secondary adsorption of U / Th by surface hydroxyl groups.

[0040] In post-processing, the core function of mechanical stirring is to achieve non-destructive deagglomeration of soft agglomerates and homogenization of uranium ions through laminar shear force in a liquid environment: it generates gentle shear at a low speed of 200~300 rpm, breaking down hydrogen-bonded pseudo-agglomerates (>50μm) in the slurry before dehydration, while promoting the uniform dispersion of residual uranium ions (<0.1ppm) in the water, avoiding the risk of local enrichment of uranium on the powder surface during drying, and providing a pre-dispersed and homogeneous basis for subsequent air jet milling.

[0041] Post-deagglomeration processing achieves the breaking down of soft agglomerates and precise particle size control. Utilizing an integrated airflow milling-classification system, soft agglomerates formed after hydrothermal treatment are eliminated, restoring the single-particle dispersion state and ensuring D100 ≤ 50μm and stable D50 distribution to meet the requirements of high-filling, low-viscosity packaging processes. During airflow milling, the compressed air pressure is 0.6~0.8MPa, Mach number > 1.8, resulting in high-speed collisions between particles with gentle shear force, preserving the spherical morphology. The online classification system incorporates a high-efficiency centrifugal rotor, achieving a classification particle size accuracy of ±2μm. Oversized particles are immediately returned to the milling zone, resulting in a product recovery rate > 98%.

[0042] In the manufacturing process of this invention, the finished spherical alumina powder is used as a filler in the resin sealing materials of highly integrated integrated circuits, large-scale integrated circuits, and very large-scale integrated circuits, which can prevent operational failures of memory devices caused by alpha rays. The finished spherical alumina powder (U < 30 ppb, sphericity > 95%, D50 1~30 µm), after being deeply deuranced using this process, is designed as a thermally conductive filler for high-end IC packaging, blocking the source of alpha rays and synergistically improving packaging performance.

[0043] A three-stage uranium removal system, consisting of cascade acid washing, hydrothermal enhancement, and particle size distribution, was used to stably control the uranium content below 10 ppb, corresponding to an alpha particle flux of <0.001 cm⁻¹. -2 h -1 This is significantly lower than the DRAM soft error sensitivity threshold (0.01 cm⁻¹). -2 h -1 Thus eliminating the problem at its source. 238 The 4.2 MeV α particles generated by the U decay chain interfere with the charge of the storage node.

[0044] High sphericity (>95%) and high filler content (up to 85wt% in resin systems) synergistically reduce encapsulation thermal resistance, alleviate interfacial delamination caused by thermal stress, and indirectly reduce additional soft errors induced by thermal cycling. After low-temperature drying and airflow pulverization, the powder D100 ≤ 50µm ensures low viscosity and high flowability during encapsulation, avoiding scratches on metal wiring or filling voids caused by large particles.

[0045] In summary, the present invention has the following beneficial effects: 1. Unlike traditional flame spheroidization followed by a single acid wash, which can only reduce uranium to 20-30 ppb, this invention uses a three-stage synergistic uranium removal system of strong acid open circuit + deep oxidation of weak acid + hydrothermal enhancement to peel off uranium in three states: free, adsorbed, and lattice, layer by layer, so that the finished product is stable at ≤10 ppb, filling the industrialization gap of ultra-low alpha ray spherical alumina. 2. Unlike conventional processes that separate spheroidization and uranium removal into two stages, where the dense spheroidization layer hinders acid penetration, this invention introduces gradient acid washing immediately after spheroidization, utilizing newly formed cracks and micropores as acid channels to achieve seamless connection between spheroidization and uranium removal, significantly shortening the process and reducing secondary wrapping. 3. The production process of this invention introduces a quantitative model of particle size and uranium residue into the gradation for the first time. Uranium in particles >45μm is enriched by 3 to 5 times and removed by a combination of wet cyclone / centrifugation. Small and medium-sized powders are precisely proportioned according to specific surface area, which not only ensures the filling rate but also inhibits uranium re-adsorption, thus achieving coupled control of physical classification and chemical purity. 4. The production process of this invention protects the integrity of the powder at low temperatures throughout the entire process. The entire process of dehydration, drying and depolymerization is ≤120℃, which avoids pore closure and uranium re-encapsulation caused by high-temperature sintering. Airflow pulverization replaces ball milling, maintaining sphericity >95%, and the powder filling rate in epoxy molding compound can reach 85wt%, effectively reducing thermal resistance. 5. The production process of high-purity, low-uranium-content spherical alumina powder of this invention achieves resource closed-loop and green manufacturing. Among them, the coarse particles retained in the grade are 100% recycled and re-spheroidized; the nitric acid waste liquid is recycled in a gradient manner, effectively reducing the amount of waste acid; the whole process is free of high-temperature calcination and organic solvents, meeting the dual requirements of environmental protection and consistency of materials for 3nm node chips. Detailed Implementation

[0046] This specific embodiment is merely an explanation of the present invention and is not intended to limit the invention. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they are within the scope of the claims of the present invention.

[0047] Example 1

[0048] Step 1. Provide angular alumina micro powder raw material with a uranium content of 58 ppb and a D50 of 25 μm; Step 2. Flame melting and spheroidizing treatment to obtain primary spherical alumina powder; Step 3. Step-by-step chemical acid washing and purification: First-stage pickling: Adjust the pH of the slurry to 1.3 using 4 mol / L hydrochloric acid, and stir at 70°C for 2 hours. Second-stage pickling: After washing, the pH of the slurry is adjusted to 3.0 using 1 mol / L nitric acid, and the mixture is stirred at 80°C for 4 hours. Step 4. Hydrothermal enhanced uranium removal: Add an appropriate amount of deionized water, control the solid-liquid ratio to 1:10 w / w, react at 170℃ for 4.5 hours, cool naturally after the reaction, remove the slurry, and wash it thoroughly with deionized water until neutral. Step 5. Wet grading technology is adopted, using hydrocyclones and centrifugal sedimentation classifiers to remove large particles with a particle size greater than 45μm, and the particles are graded according to the target particle size distribution with a gradation ratio of coarse:medium:fine = 70:15:15. Step 6. Dehydrate the graded powder, then perform spray drying and air pulverization at an inlet temperature of 115°C and a pressure of 0.7 MPa to obtain the finished spherical alumina powder.

[0049] Example 2

[0050] Step 1. The angular alumina micro powder raw material has a uranium content of 58 ppb and a D50 of 10 μm; Step 2 is the same as in Example 1; Step 3. Step-by-step chemical acid washing and purification: First-stage pickling: Adjust the pH of the slurry to 1.5 using sulfuric acid with a concentration of 2 mol / L, and stir the reaction at 50°C for 3 hours; Second-stage pickling: After washing, the pH of the slurry is adjusted to 4.0 using a 1:1 mixture of 0.5 mol / L hydrochloric acid and nitric acid, and the mixture is stirred at 90°C for 4 hours. Step 4. Hydrothermal enhanced uranium removal: Add an appropriate amount of deionized water, control the solid-liquid ratio to 1:15 w / w, and react at 165℃ for 5 hours; Steps 5 and 6 are the same as in Example 1, resulting in finished spherical alumina powder.

[0051] Example 3

[0052] Steps 1, 2, and 3 are the same as in Example 1; Step 4. Hydrothermal enhanced uranium removal: Add an appropriate amount of deionized water, control the solid-liquid ratio to 1:5 w / w, and react at 175℃ for 4 hours; Step 5 is the same as in Example 1; Step 6. Dehydrate the graded powder, vacuum dry at 60℃ / 5kPa and then process it with airflow pulverization to obtain the finished spherical alumina powder.

[0053] Example 4

[0054] Step 1. The angular alumina micro powder raw material has a uranium content of 55 ppb and a D50 of 25 μm; Step 2 is the same as in Example 1; Step 3. Step-by-step chemical acid washing and purification: First-stage pickling: Adjust the pH of the slurry to 1.2 using 4 mol / L nitric acid, and stir at 75°C for 1.5 hours; Second-stage pickling: After washing, the pH of the slurry is adjusted to 2.5 using 0.5 mol / L nitric acid, and the mixture is stirred at 85°C for 4 hours. Step 4. Hydrothermal enhanced uranium removal: Add an appropriate amount of deionized water, control the solid-liquid ratio to 1:8 w / w, and react at 168℃ for 5 hours; Step 5. Use wet grading technology to remove large particles with a particle size greater than the target D90 value, and perform gradation according to the target particle size distribution; Steps 5 and 6 are the same as in Example 3, resulting in finished spherical alumina powder.

[0055] Example 5

[0056] Step 1. The angular alumina micro powder raw material has a uranium content of 59 ppb and a D50 of 60 μm; Step 2 is the same as in Example 1; First-stage pickling: Adjust the pH of the slurry to 1.0 using sulfuric acid with a concentration of 5 mol / L, and stir the reaction at 80℃ for 2 hours; Second-stage pickling: After washing, the pH of the slurry is adjusted to 3.2 using 1 mol / L nitric acid, and the mixture is stirred at 90°C for 4 hours. Steps 4, 5, and 6 are the same as in Example 4, resulting in the finished spherical alumina powder.

[0057] Comparative Example 1 Step 1 is the same as in Example 1; Step 2. Dry spheroidization, reaction in a high-temperature rotary kiln at 1600℃ for 2 hours; Step 3. Single-stage acid washing and purification: Adjust the pH of the slurry to 1.3 using 4 mol / L hydrochloric acid, and stir the reaction at 70℃ for 5 hours; Steps 4, 5, and 6 are the same as in Example 1, resulting in finished spherical alumina powder.

[0058] Comparative Example 2 Steps 1, 2, and 3 are the same as in Example 1; Step 4. Use dry sieving to remove particles >50μm, ensuring uniform particle size and no particle size distribution; Step 5. The sieved powder is directly dried and deagglomerated. After reacting at 250°C in a rotary kiln for 2 hours, it is mechanically pulverized using a ball mill at 200 rpm for 1 hour to obtain the finished spherical alumina powder.

[0059] The finished spherical alumina powders prepared in Examples 1-5 and Comparative Examples 1-2 were subjected to performance tests, including: uranium content, sphericity, particle size distribution, filling rate, thermal resistance, and alpha ray flux.

[0060] 1. Detection Method Uranium content: ICP-MS (inductively coupled plasma mass spectrometry), detection limit ≤ 0.1 ppb, sample digested with HF + HNO3.

[0061] Sphericity: SEM image analysis + ImageJ sphericity algorithm, counting ≥300 particles.

[0062] Particle size distribution: Laser particle size analyzer (Malvern Mastersizer 3000), wet dispersion, water as the medium.

[0063] Filling ratio: The powder is incorporated into the epoxy resin, vacuum degassed, cured, and the mass fraction is calculated by weighing.

[0064] Thermal resistance: ASTM D5470 standard, thermal conductivity converted to thermal resistance value, encapsulation layer thickness 100μm.

[0065] Alpha flux: Ultra-low background alpha particle counter (CANBERRA Alpha Analyst), measurement time ≥24h, statistical error <5%.

[0066] 2. Test Results Table 1 Summary of Performance Test Results for Each Finished Spherical Alumina Powder

[0067] Results analysis: The comparison of the performance test results of the examples and comparative examples shows that the production process of the present invention, which is "flame melting spheroidization - step-by-step acid washing - hydrothermal enhancement - wet classification - low temperature gas flow depolymerization", has shown systematic advantages in actual verification. It can stably compress the uranium content to below 30 ppb while maintaining the high sphericity and excellent dispersibility of the powder, thereby bringing about an overall leap in packaging performance.

[0068] First, based on the key indicator of uranium content, the detection values ​​of Examples 1-5 ranged from 3.2 to 6.9 ppb, all below the 30 ppb limit and below 10 ppb, with a fluctuation range of only ±2.8 ppb, demonstrating the repeatability and robustness of the process. In contrast, Comparative Example 1, using traditional single-stage acid washing, and Comparative Example 2, further omitting hydrothermal treatment and classification, showed uranium residues as high as 28.5 ppb and 35.1 ppb, respectively. This difference clearly demonstrates that only the three-stage uranium removal strategy of "strong acid stripping—weak acid oxidation—high-temperature and high-pressure hydrothermal treatment" can effectively strip and stably remove uranium from deep within the crystal lattice, surface adsorption, and large particle enrichment nuclei in a single step; the absence of any step will significantly weaken the uranium removal depth, leading to loss of control over the final indicator.

[0069] Secondly, regarding morphology control, flame melting and spheroidization imparts extremely high initial sphericity to the particles, while subsequent low-temperature airflow deagglomeration completely breaks down soft agglomerates without damaging the surface, stabilizing the sphericity of Examples 1-5 at 97.8-99.1%. Comparative Example 1 uses dry spheroidization, where particles undergo secondary sintering in a high-temperature rotary kiln, resulting in surface passivation and regeneration of sharp edges, reducing sphericity to 88.3%. Comparative Example 2 directly uses a ball mill for mechanical pulverization, where intense shearing forces completely destroy the spherical structure, further decreasing sphericity to 82%. This morphological deterioration not only reduces powder flowability but also increases porosity during subsequent encapsulation, directly raising thermal resistance.

[0070] The particle size distribution data further revealed the value of classification accuracy. In Examples 1-4, the raw material D50 was between 10 and 25 μm. After two-stage classification using wet cyclone-centrifugal sedimentation, D100 was strictly limited to within 48.3 μm, and coarse tails >45 μm were completely removed; this particle size range showed a 3-5 times enrichment in uranium. In Example 5, due to the raw material D50 being as high as 60 μm, although the process parameters were the same, D100 still reached 64.2 μm, resulting in a relatively high uranium residue (6.9 ppb). Comparative Examples 1-2 did not introduce wet classification, and coarse tails were not removed, resulting in severe tailing in the overall particle size distribution. The uranium enrichment nucleus residue directly increased the overall content.

[0071] There is a strong negative correlation between filler content and thermal resistance. Examples 1-4, thanks to their high sphericity and reasonable gradation, achieved filler contents of 83.7-85.3 wt% in the epoxy system, corresponding to thermal resistances as low as 0.121-0.130 K·cm. 2 / W; In Example 5, due to the larger particle size, the filling rate decreased slightly to 82.1%, and the thermal resistance increased to 0.141 K·cm. 2 / W. Comparative Examples 1 and 2, due to poor sphericity and uneven particle size, had filling rates of only 68.3% to 72.1%, while their thermal resistances increased to 0.172 and 0.210 K·cm, respectively. 2 / W, with an increase of 40-60%. This indicates that in high-end packaging applications, thermal management is extremely sensitive to powder morphology and particle size, and any minute defects will be amplified exponentially.

[0072] The alpha-ray flux data showed a linear correlation with uranium content. The flux distributions in Examples 1-5 ranged from 0.0006 to 0.0009 cm⁻¹. -2 h -1 This is far below the DRAM soft error sensitivity threshold (0.01cm). -2 h -1 ), cutting off the source 238 The 4.2 MeV α particles generated by the U decay chain interfere with the storage nodes. The flux in Comparative Examples 1 and 2 reaches 0.0023–0.0028 cm⁻¹. -2 h-1 It has approached the upper limit of the threshold, and there is a risk of soft errors if it is run for a long time.

[0073] Based on the above results, the three-stage uranium removal system of Examples 1-5 of the present invention, which involves tiered acid washing, hydrothermal enhancement, and particle size distribution, is significantly superior to the traditional single treatment method. It achieves comprehensive performance of ultra-low uranium, high sphericity, high filling capacity, low thermal resistance, and zero alpha-ray soft error, and is suitable for the ultra-high purity packaging material requirements of 3nm and below nodes.

Claims

1. A production process for high-purity, low-uranium-content spherical alumina powder, characterized in that, Includes the following steps: Step 1. Provide alumina and aluminum hydroxide micro powder raw materials with uranium content of 50~100ppb and D50 of 1~100μm; Step 2. The alumina micro powder and aluminum hydroxide micro powder are subjected to flame melting and spheroidization treatment to obtain primary spherical alumina powder; Step 3. Purify the primary spherical alumina powder obtained in Step 2 by step-by-step chemical acid washing or alkali washing; Step 4. Perform hydrothermal enhanced uranium removal on the powder obtained in Step 3: hydrothermal reaction at 150~180℃ for 3~12 hours, followed by thorough washing; Step 5. Perform particle size sorting and gradation on the powder obtained in Step 4: remove large particles and grade them according to the target particle size distribution; Step 6. Dehydrate, dry and post-process the graded powder to obtain finished spherical alumina powder with a uranium content between 1 and 30 ppb.

2. The production process according to claim 1, characterized in that, Step 3, acid washing and purification, includes the following specific steps: Step 3.1 First-stage pickling: Adjust the pH of the slurry to ≤2.0 using an acid solution with a concentration of 2~6 mol / L, and stir the reaction at 50~80℃ for 1~6 hours; Step 3.2 Second-stage pickling: After washing, adjust the pH of the slurry to 2.0-4.0 using inorganic or organic acid with a concentration of 0.5-2 mol / L, and stir the reaction at 60-90℃ for 4-12 hours; Step 3.3: Wash thoroughly after pickling.

3. The production process according to claim 2, characterized in that, The acid mentioned in step 3.1 is hydrochloric acid, nitric acid, sulfuric acid, or an organic acid, with the pH adjusted to ≤1.5; the inorganic acid mentioned in step 3.2 is nitric acid or a mixture of hydrochloric acid and nitric acid. The thorough washing described in step 3.3 specifically includes: after each stage of acid washing, washing with a large amount of deionized water 3 to 8 times until the washing solution is close to neutral and the conductivity meets the standard, so as to completely remove residual acid radical ions and dissolved impurity ions.

4. The production process according to claim 1, characterized in that, In step 4, the hydrothermal reaction temperature is 165~175℃ and the reaction time is 4~12 hours.

5. The production process according to claim 1 or 4, characterized in that, Step 4 specifically includes: transferring the powder slurry, which has been purified by stepwise acid washing and thoroughly washed, into a high-pressure reactor, adding an appropriate amount of deionized water, and controlling the solid-liquid ratio to be 1:2~1:15 w / w; carrying out a hydrothermal reaction at a temperature of 165~175℃ for 4~12 hours; after the hydrothermal reaction is completed, allowing it to cool naturally, removing the slurry, and washing it thoroughly with deionized water again until it is neutral.

6. The production process according to claim 1, characterized in that, The removal of large particles in step 5 refers to the removal of particles with a diameter greater than the target D97~D100 value; the particle size distribution is optimized by taking into account the specific surface area of ​​powders with different particle sizes and the risk of impurity residue.

7. The production process according to claim 1 or 6, characterized in that, Step 5, which involves removing large particles, specifically includes: using wet classification technology to remove particles larger than the target value D97~D100 from the powder slurry that has been washed after hydrothermal treatment; the wet classification technology includes hydrocyclones and centrifugal sedimentation classifiers.

8. The production process according to claim 1, characterized in that, The dehydration operation in step 6 includes pressure filtration and centrifugal filtration; the drying is low-temperature drying, including spray drying and vacuum drying; the post-treatment is depolymerization treatment, including mechanical stirring and air jet milling.

9. The production process according to any one of claims 1 to 8, characterized in that, The finished spherical alumina powder is used as a filler in resin sealing materials for highly integrated integrated circuits, large-scale integrated circuits, and ultra-large-scale integrated circuits, and can prevent operational failures of memory devices caused by alpha rays.

Citation Information

Cited By

  • Low-radioactivity spherical aluminum oxide for POP packaging and preparation method of low-radioactivity spherical aluminum oxide

    CN116924441A